Survey on morphological - anatomycal characteristics and antioxidant activity of Eclipta prostrata L. - Vo , Văn Hiếu; Le , Văn Út (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
Eclipta prostrata L. is a member of the Asteraceae plant family and inhabited in tropical or subtropical regions of the world. E. prostrata has liver-protective effects, anti-venom properties against snake venom, antioxidant properties, promotes hair growth, and aids in wound healing,... In this study, the morphology and anatomy of E. prostrata were studied. Beside that, the antioxidant activity of E. prostrata was investigated. E. prostrata was identified by comparing its morphological characteristics with botanical descriptions found in various documents and the Vietnamese pharmacopoeia V. Photograph and describe the morphological and anatomical characteristics. The microstructure of the stem and leaves was stained with alum carmine and iodine green dyes. Qualitative analysis of active compounds was performed using the Cuilei method. The 2,2-Diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity was used to determine antioxidant potential. Morphology: herbs, circular cross section. Leaves opposite, simple. Anatomy: Young stems usually circular, collenchyma was present usually under the epidermis. The soft extract of E. prostrata contains active ingredients including saponins, flavonoids, coumarins, and tannins. The antioxidant activity of the E. prostrata extract was determined using the DPPH free radical scavenging method, showing good antioxidant activity with an IC50 value of 54.898 μg/ml. Thus, the morphological and anatomical characteristics of E. prostrata, as well as the antioxidant activity of its extract, were investigated.